2019
DOI: 10.3390/cells8080770
|View full text |Cite
|
Sign up to set email alerts
|

Structural Consequences of Copper Binding to the Prion Protein

Abstract: Prion, or PrPSc, is the pathological isoform of the cellular prion protein (PrPC) and it is the etiological agent of transmissible spongiform encephalopathies (TSE) affecting humans and animal species. The most relevant function of PrPC is its ability to bind copper ions through its flexible N-terminal moiety. This review includes an overview of the structure and function of PrPC with a focus on its ability to bind copper ions. The state-of-the-art of the role of copper in both PrPC physiology and in prion pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 157 publications
(207 reference statements)
0
49
0
Order By: Relevance
“…Indeed, from numerous metal ions tested (including Cu 2+ ), Zn 2+ alone could induce Tau protein condensates, another prime causative agent of neurodegenerative disease deposits [ 14 ]. The cellular prion protein also binds to both Zn 2+ and Cu 2+ , with both metals inducing structural changes and decreased solubility [ 140 ] and differentially affecting its fold variants [ 141 , 142 ], where Cu 2+ -binding induces protease resistant variants [ 143 , 144 ]. Relevant to viruses existing in cells and tissues, in plasma and in external environments, studies comparing competitive binding of Cu ions to peptides containing both cysteines (e.g., ZnFs) and arginines (e.g., RRMs), Cu ions were found to preferentially bind to arginine, lysine, and histidine in the gas phase [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, from numerous metal ions tested (including Cu 2+ ), Zn 2+ alone could induce Tau protein condensates, another prime causative agent of neurodegenerative disease deposits [ 14 ]. The cellular prion protein also binds to both Zn 2+ and Cu 2+ , with both metals inducing structural changes and decreased solubility [ 140 ] and differentially affecting its fold variants [ 141 , 142 ], where Cu 2+ -binding induces protease resistant variants [ 143 , 144 ]. Relevant to viruses existing in cells and tissues, in plasma and in external environments, studies comparing competitive binding of Cu ions to peptides containing both cysteines (e.g., ZnFs) and arginines (e.g., RRMs), Cu ions were found to preferentially bind to arginine, lysine, and histidine in the gas phase [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence suggesting that Cu may be involved in the conformational conversion of PrP C and the transmission of prion diseases. When Cu binds to the octarepeat region of a flexible N-terminal domain, Cu interacts and crosslinks with the α-helix-rich C-terminal domain and changes it to a β-sheet rich PrP Sc [ 27 ]. Giachin et al suggested that the non-octarepeat Cu binding site is also a key regulator of the conversion of PrP C [ 28 ].…”
Section: Functions Of Normal Cellular Prion Protein and Neurometalmentioning
confidence: 99%
“…PrP C has the ability to bind copper ions through its flexible N-terminal domain. This specific binding seems to mediate structural changes in PrP C moiety, stabilizing interactions between the N- and C-terminal regions, which may play a role as transporter and sensor of metal ions [ 71 ]. Interestingly, the aforementioned LRP1 also participates in PrP C Cu 2+ -mediated endocytosis from lipid rafts in neuronal cells, when its octapeptide repeats domain is fully loaded with copper ions [ 61 ].…”
Section: Prp C In Intracellular Traffickingmentioning
confidence: 99%